Endoscopic surgery for spontaneous supratentorial intracerebral haemorrhage: A systematic review and meta-analysis - Hallenberger, Tim J.; Guzman, Raphael; Bonati, Leo H.; Greuter, Ladina; Soleman, Jehuda (Frontiers in Neurology, 2022)
Introduction: Treatment for spontaneous supratentorial intracerebral haemorrhage (SSICH) is limited and consist of either best medical treatment (BMT) or surgical hematoma evacuation. Treatment methods and choice of surgical technique are debated, and so far, no clear advantage of endoscopic surgery (ES) over conventional craniotomy (CC) or BMT was shown. The aim of this systematic review and meta-analysis was to investigate the differences in outcome, morbidity, and mortality between ES and CC or BMT. Methods: We systematically searched Embase and PubMed databases for randomized controlled trials comparing ES to CC or BMT. The primary outcome was favourable functional outcome after 6 months. Secondary outcomes were morbidity and mortality rates and duration of surgery. Results: Seven articles were eligible for the outcome analysis with 312 subjects in the control (216 CC, 96 BMT) and 279 in the treatment group (ES). Compared to BMT, ES showed significantly improved favourable functional outcome (RR 1.93[1.12;3.33], p=0.02) and mortality rates (RR 0.63[0.44;0.90], p=0.01). No significant difference in favourable functional outcome and mortality was seen in ES compared to CC (RR 2.13[0.01;737], p=0.35; RR 0.42[0.17;1.05], p=0.06). ES showed significantly lower morbidity (RR 0.41[0.29;0.58], p<0.01), and infection rates (RR 0.33[0.20;0.54], p<0.01) compared to CC. Duration of surgery was significantly shorter for ES compared to CC (SMD -3.17[-4.35;-2.00], p<0.01). Conclusion: ES showed significantly improved favourable functional outcome and mortality rates compared to BMT while showing reduced length of surgery and lower complication rates compared to CC. Therefore, ES appears a promising approach for treatment of SSICH justifying further prospective trials.